1996
DOI: 10.1139/v96-253
|View full text |Cite
|
Sign up to set email alerts
|

Redox activity of tryptophan residues in recombinant cytochrome c peroxidase and its W51F and W191F mutants

Abstract: Tryptophan oxidation mediated via the heme was initiated by adding 2, 6, and 20 equivalents of H20, to 5 p,M recombinant CCP (CCP(M1)) and its W5 IF and W191F mutants at pH 7.0. Addition of the proteins to 8 M urea (pH 1.5) relieved heme quenching of Trp fluorescence. CCP(M1)-I, W5 1F-I, and W 191F-I, the two-electron oxidized species (F~'~=O,R'+) formed on addition of 2 equivalents of H,02, exhibited decreased fluorescence relative to the ~e " ' forms. Loss of 0.7 Trp in CCP(M1)-I and W5 1F-I, and 0.2 Trp in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 28 publications
(30 reference statements)
2
15
0
Order By: Relevance
“…Building on previous studies 16–23,26,3235 that pinpointed a limited number of donors to the heme in the endogenous oxidation of Ccp1 by H 2 O 2 , here we identify an unprecedented number of donor residues (24) by characterizing their stable end products by in-depth LC-MS/MS analysis. This large number of proximal and distal donors delineates numerous hole-hopping pathways emanating from Ccp1's heme that protect it from irreversible modification.…”
Section: Discussionmentioning
confidence: 99%
“…Building on previous studies 16–23,26,3235 that pinpointed a limited number of donors to the heme in the endogenous oxidation of Ccp1 by H 2 O 2 , here we identify an unprecedented number of donor residues (24) by characterizing their stable end products by in-depth LC-MS/MS analysis. This large number of proximal and distal donors delineates numerous hole-hopping pathways emanating from Ccp1's heme that protect it from irreversible modification.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidation of WTCcP residues during its reaction with hydrogen peroxide has been reported. Erman observed CcP dimerization through oxidized tyrosine residues (34), and English reported the loss of tryptophan and tyrosine residues as a result of the treatment of CcP with excess hydrogen peroxide (35,37). By replacing Phe with Trp in horseradish peroxidase at the corresponding position of Trp191 in CcP, Morimoto et al observed spectral features corresponding a ferryl and a Trp radical (46).…”
Section: Discussionmentioning
confidence: 99%
“…For CcP(MI, W191F) and CcP(MI, W51F, W191F), the transiently formed compound I decays to a species containing a ferryl oxo and protein radical. The location(s) of this radical in CcP mutants containing the Trp191Phe mutation has not been unambiguously identified (34)(35)(36)(37)52). Although Trp51 has been ruled out as the primary radical site in WTCcP, its close position to the heme makes it an attractive site for the radical in the W191F mutants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that CCP and CCP W191F exhibit very different properties in vitro [12,14,[19][20][21], phenotypic comparison of ccp1D and ccp1D-ccp1 W191F yeast is of much interest. Here we compare the growth and survival of unstressed and H 2 O 2 -challenged ccp1D, ccp1D-ccp1 W191F and wild-type S. cerevisiae cells in the W303-1B genetic background.…”
Section: Introductionmentioning
confidence: 99%